Analisis Minat Belajar Siswa Terhadap Mata Pelajaran Fisika di Ma Al-Muhajirin Pandan - Lia Wahyuningsih Budiarti; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This study was intended to understand students’ interest in physics at Madrasah Aliyah AL-Muhajirin Pandan. The subject of this study is XII MIA students at Madrasah Aliyah AL-Muhajirin Pandan, while the object of this study is the interest of XII MIA students at Madrasah Aliyah AL-Muhajirin Pandan. The method used was a qualitative approach for case study. The data collection technique was questionnaire, and then the data was analyzed by using interactive model of Miles and Huberman. The analysis result shows that students' interest toward physics at Madrasah Aliyah AL-Muhajirin Pandan already has the percentage in about 70% in average. This study provides knowledge that other researchers can use to identify the unknown factors affecting students' interest in physics